2016
DOI: 10.1021/acsami.5b10493
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Carbon Nanoparticle–Carbon Nanofiber Composite as an Efficient Metal-Free Cathode Catalyst for Oxygen Reduction Reaction

Abstract: Metal-free nitrogen-doped carbon materials are currently considered at the forefront of potential alternative cathode catalysts for the oxygen reduction reaction (ORR) in fuel cell technology. Despite numerous efforts in this area over the past decade, rational design and development of a new catalyst system based on nitrogen-doped carbon materials via an innovative approach still present intriguing challenges in ORR catalysis research. Herein, a new kind of nitrogen-doped carbon nanoparticle-carbon nanofiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
124
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 64 publications
6
124
1
Order By: Relevance
“…The XRD patterns of Fe–N–C and N–C are shown in Figure a. Both samples present broad peaks at 20°–30° and 40°–50°, which are assigned to the (002) and (101) crystal faces for graphitic carbon materials (JCPDS# 41‐1487), respectively, and in consistent with the selected area electron diffraction patterns (inset in Figure c,d) . No characteristic peaks for Fe or its oxides/carbides/nitrides can be detected, and combining with TEM observation, it is confirmed that no highly crystalline Fe‐containing species exist in the Fe–N–C.…”
Section: Resultssupporting
confidence: 67%
“…The XRD patterns of Fe–N–C and N–C are shown in Figure a. Both samples present broad peaks at 20°–30° and 40°–50°, which are assigned to the (002) and (101) crystal faces for graphitic carbon materials (JCPDS# 41‐1487), respectively, and in consistent with the selected area electron diffraction patterns (inset in Figure c,d) . No characteristic peaks for Fe or its oxides/carbides/nitrides can be detected, and combining with TEM observation, it is confirmed that no highly crystalline Fe‐containing species exist in the Fe–N–C.…”
Section: Resultssupporting
confidence: 67%
“…In such systems, the plasma enables unique reactions such as C–H activation reactions at the interface between the solution and plasma, whereas conventional plasma induces random decomposition reactions. We have fabricated graphene, heterographene, nanocarbon sheets, and nanocarbon spheres via solution plasma from organic solutions containing solvents such as benzene, toluene, pyridine, or pyrazine60616263646566676869707172. Moreover, the reaction rate is substantially higher than the rates of other synthesis methods such as chemical vapor deposition and pyrolysis synthesis.…”
mentioning
confidence: 99%
“…The as-obtained S,N-Fe/N/C-CNT hybrid materials were firstly studied by X-ray diffraction (XRD) and Raman spectroscopy. [13] Meanwhile, the Raman spectrum shows two main bands located at 1591 and 1352 cm À1 that correspond to the vibration of sp 2 -bonded carbon atoms and dispersive defect-induced vibrations, respectively (Supporting Information, Figure S2). [13] Meanwhile, the Raman spectrum shows two main bands located at 1591 and 1352 cm À1 that correspond to the vibration of sp 2 -bonded carbon atoms and dispersive defect-induced vibrations, respectively (Supporting Information, Figure S2).…”
mentioning
confidence: 99%